Enhancing data governance framework for data privacy in Saudi Arabia - Alharbi, Zahyah H.; Alwahbi, Amal A.; Alqurashi, Tahani (Edelweiss Applied Science and Technology, 2026)
This study evaluates data governance framework implementation in the Kingdom of Saudi Arabia, with particular emphasis on identifying data privacy challenges and proposing enhancement strategies. A qualitative research approach was employed, conducting semi-structured interviews with thirteen participants from private, government, and semi-government organizations that have implemented DAMA-DMBOK-based data governance frameworks. Thematic analysis was used to identify implementation challenges and improvement areas. Four primary challenges emerged: insufficient organizational awareness of data governance value, difficulties complying with international data protection regulations (particularly GDPR), inadequate data classification practices, and stakeholder resistance due to conflicts of interest. While framework adoption remains incomplete, participants recognize the need for enhancement through three strategic interventions: clearly defining strategic and operational objectives, increasing organizational awareness while developing human and technical resources, and strengthening data privacy through proactive integration into system design phases. This research provides actionable recommendations for Saudi organizations and policymakers to facilitate effective data governance implementation, emphasizing the balance between data protection requirements and organizational innovation needs.